Dukungan sosial dan kualitas hidup orang dengan HIV/AIDS - Mardia Mardia; Riris Andono Ahmad; Bambang Sigit Riyanto (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Quality of life among people living with HIV/AIDS based on criteria diagnosis and other factors in Surakarta PurposeThis study aimed to determine the quality of life among people living with HIV/AIDS based on the criteria for diagnosis and other factors.MethodsThis study was conducted in the VCT clinic hospital of Dr. Moewardi. The population was HIV-positive patients with antiretroviral therapy. Data collection conducted through medical records and interview to patients. ResultsOut of a total of 89 respondents, 66.29% were males and 71.91% were aged between 26-45 years. We found significant correlations for diagnosis of HIV/AIDS, opportunistic infections, time since HIV diagnosis, duration of ARV therapy, social support, modes of transport, sex, age, and marital status with the quality of life. Multivariate analysis obtained by each variable showed the strongest association with the quality of life was time since diagnosis, social support and duration of ARV therapy. ConclusionThe quality of life was better for those who have been diagnosed with HIV/AIDS ≥ 32 months, with social support, and who have been undergoing antiretroviral therapy ≥ 29 months. Improved counseling in the early days of ARV therapy is necessary to always maintain the treatment and provide support for their social life.